Don Charles Foote (1931-1969) - Baird, P.D. (ARCTIC, 1969)
In the tragic death at the age of thirty-seven of Don Foote, the Institute has lost one of its more recent active Fellows, the polar world has lost a vital force in geographical research, and his friends have lost a well-loved man. One is agonised by the stroke of fate which permits a man to live life dangerously in the Arctic, travelling by dog team, tossing in small boats, walking through sub-zero blizzards, and then allows him to be struck down by that modern civilised killer, the automobile. . Don was a product of Dartmouth College, which above all institutions in the United States has given so much to northern enterprise, including the first Executive Director of the Institute, and many subsequent Governors and Fellows. From there, we know, come not only well-trained and intelligent graduates, such as other American Universities produce, but above all real men. Don was such a man, powerful physically, a well-rounded human person, a leader who led by his personality rather than by his intellectual status which was indeed high. His early research work, stimulated by Dr. Trevor Lloyd, was in far northern Europe. He was a Summer Scholar at the University of Oslo and spent two further years travelling and working in high subarctic Scandinavia and Spitsbergen. Then he came to McGill University, where as a student taking higher degrees, and later as a member of staff, he spent the best part of ten years, and became, despite his youth, the doyen of arctic studies in the field of Human Geography. During this time his areas of research lay in Alaska and later Baffin Island. In Alaska his prime concern was with the economic base of the Eskimo hunter, caribou, whales, bears and seals. As a dedicated conservationist he was appointed in 1966 by the Canadian Government to head an Area Economic Survey of Baffin Island, and two years later under the International Biological Programme to study the 'adaptability' of the Igloolik people. Then came a sabbatical leave to join the University of Alaska's social research programme; ...